COMMUNICATION CONTROL METHOD FOR COMMUNICATION TERMINAL DEVICE, AND COMMUNICATION TERMINAL DEVICE - YOSHINAGA, TAKEKAZU; ISHII, TAKAHITO (2016)
The purpose of the present invention is to avoid an inoperative state caused by excessive power consumption when a plurality of communication units corresponding to different communication schemes or different communication systems are implemented in a communication terminal device and are made to perform communication in parallel. Consequently, this communication control method for a communication terminal device is for controlling communication of a communication terminal device communicating in parallel at a plurality of communication units corresponding to different communication schemes or communication systems, and is characterized by comprising: a step in which a first communication unit, during transmission, stops transmission and receipt by a different communication unit; and a step in which a transmission and receipt stop duration of the different communication unit is maintained at or below a predetermined number of synchronization protection stages. La présente invention a pour objet d'éviter un état inopérant causé par une consommation énergétique excessive lorsqu'une pluralité d'unités de communications correspondant à des schémas de communication différents ou à des systèmes de communication différents est mise en œuvre dans un dispositif de terminal de communications et qu'elle est amenée à effectuer une communication en parallèle. Par conséquent, le présent procédé de commande de communications pour un dispositif de terminal de communications est destiné à commander la communication d'un dispositif de terminal de communications communiquant en parallèle au niveau d'une pluralité d'unités de communications correspondant à des schémas de communication ou à des systèmes de communication différents, et est caractérisé en ce qu'il comporte: une étape lors de laquelle une première unité de communications, pendant l'émission, arrête l'émission et la réception par une unité de communications différente; et une étape lors de laquelle une durée d'arrêt d'émission et de réception de l'unité de communications différente est maintenue inférieure ou égale à un nombre prédéterminé d'étages de protection de synchronisation. 本発明の目的は、異なる通信方式あるいは通信システムに対応した複数の通信部を通信端末装置に実装かつ並行して通信を行う場合に、消費電力超過による動作不能を回避することにある。そこで、本発明の通信端末装置の通信制御方法は、異なる通信方式あるいは通信システムに対応した複数の通信部で並行して通信を行う通信端末装置の通信制御方法であって、第１の通信部が送信時に他の通信部の送受信を停止させるステップと、前記他の通信部の送受信停止期間を所定の同期保護段数以下にするステップとを有することを特徴とする。